Handball in school: teaching of defensive contents - MENEZES,RAFAEL P. (2021)
Abstract This study aimed to identify the defensive contents and teaching approaches preferred by handball coaches of school teams. Eleven coaches from a city in the State of São Paulo were interviewed. The discourses from the semi-structured interviews were analyzed based on the Collective Subject Discourse method. Coaches revealed that match-up, base position, coverage, and spatial occupation are the main individual defensive contents and use the teaching through games situations, technique approach, and teaching through games. The main group defensive content mentioned by the coaches is the match-up changes, mutual cover, and defensive systems, for which they preferred the teaching through games situations, teaching through games and technique approach. The findings show that although they are content of the same phase of the game, there is a preference for different teaching approaches. On the other hand, there seems to be inconsistency with the choice of the technique approach when it comes to the teaching of individual defensive contents, mainly because they are related to the players’ decision-making. Such findings will contribute to the teaching of handball in school teams and with reflections for the teaching of the different specific contents, raising new discussions.